Diagnostic value of whole body diffusion-weighted MRI compared to computed tomography for pre-operative assessment of patients suspected for ovarian cancer. (September 2017) - Michielsen, Katrijn; Dresen, Raphaëla; Vanslembrouck, Ragna; De Keyzer, Frederik; Amant, Frédéric; Mussen, Elvier; Leunen, Karin; Berteloot, Patrick; Moerman, Philippe; Vergote, Ignace; Vandecaveye, Vincent
Abstract: Background: Despite excellent per-lesion performance for peritoneal staging, the additional clinical value of diffusion-weighted magnetic resonance imaging (DWI/MRI) compared to computed tomography (CT) remains to be established in ovarian cancer. Our purpose was to evaluate whole body (WB)-DWI/MRI for diagnosis, staging and operability assessment of patients suspected for ovarian cancer compared to CT. Methods: One hundred and sixty-one patients suspected for ovarian carcinoma underwent 3 T WB-DWI/MRI and contrast-enhanced CT. WB-DWI/MRI and CT were compared for confirmation of the malignant nature and primary origin of the ovarian mass, Fédération Internationale de Gynécologie et d'Obstétrique (FIGO) staging and prediction of incomplete resection using institutional operability criteria. Interobserver agreement between two readers was determined for WB-DWI/MRI and CT. Results: WB-DWI/MRI showed a significantly higher accuracy than CT (93 versus 82%, p = 0.001) to confirm the malignant nature of the ovarian mass and correctly identified 26 of 32 (81%) cancers of non-ovarian origin compared to 10/32 (31%) for CT (p < 0.001). WB-DWI/MRI assigned more ovarian carcinoma patients to the correct FIGO stage (82/94, 87%) compared with CT (33/94, 35%). For prediction of incomplete resection, WB-DWI/MRI showed significantly higher sensitivity (94 versus 66%), specificity (97.7 versus 77.3%) and accuracy (95.7 versus 71.3%) compared to CT (p < 0.001). Interobserver agreement was almost perfect (κ = 0.90) for WB-DWI/MRI and moderate (κ = 0.52) for CT for prediction of incomplete resection. Conclusions: WB-DWI/MRI was superior to CT for primary tumour characterisation, staging and prediction of incomplete resection in patients suspected for ovarian cancer. Highlights: Whole body diffusion-weighted magnetic resonance imaging (WB-DWI/MRI) improves primary tumour characterisation compared to computed tomography (CT). WB-DWI/MRI detects surgically critical metastases significantly better than CT. WB-DWI/MRI particularly improves detection of serosal and distant metastases. WB-DWI/MRI is superior to CT for operability assessment in ovarian cancer.